ETHNOMEDICINES OF HIGHLY UTILIZED PLANTS IN THE TEMPERATE HIMALAYAN REGION - Begum, Shaheen; AbdEIslam, Naser M; Adnan, Muhammad; Tariq, Akash; Yasmin, Azra; Hameed, Rukiya (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Himalayan region of Pakistan has been known as a rich source for valuable medicinal plants. The present work is the documentation of indigenous knowledge of highly utilized plants as natural remedy by the local inhabitants of the northwest part of the country. Methodology: Data on highly utilized medicinal plants were collected during May-September 2012 using semi-structured questionnaire from the elders, local herbalists and medicinal plants collectors. Results: In total about 53, plants belonging to 38, families were highly utilized in the study area, of which majority of those (43), were medicinal plants. The most frequent part used in preparation of different medicinal remedies is leaves (53%). Most of the medicinal plant species (14) were used as antipyretic. The inhabitants of the study area were producing ethno-medicines mostly in crushed form (26%). Most of the remedies (74%), were taken orally within the study area. Ten species were found most valuable from the local’s perspective such as Bergenia ciliata, Hedera nepalensis and Viola canescens. Conclusion: In conclusion, traditional healers depend largely on naturally growing medicinal plant species, which are under severe threat. This study can provide a basis for further phyto-chemical and pharmacological studies on the region’s medicinal plants. Moreover, documentation of indigenous recipes would serve as preservation of the knowledge for the generations to come.